ROLE OF RELATIONSHIP QUOTIENT ON MARITAL WELL-BEING - FASHIYA.P.S. AND C.JAYAN (ZENITH International Journal of Multidisciplinary Research, 2015)
The study examined the role of relationship quotient on marital well-being. It was hypothesized that low, moderate and high groups of relationship quotient will differ on marital well- being. The sample included 172 married people who were randomly drawn from various districts of Kerala irrespective of their age and duration of marriage. They were asked to report their responses for marital well-being inventory and Relationship Quotient Inventory. One-way ANOVA and post HOC Scheffe were conducted for hypothesis testing. From the results, hypothesis was found to be accepted there. ie, there is a significant difference in the three groups of relationship quotient on marital well-being. So it is concluded that it is better to acquire the skills on relationship quotient before marriage itself for a better relationship.